Paintings to be looked at: an effort to unify concept, form, and process - Reasor, Michael Reuben, author; Dietemann, David L., advisor; Twarogowski, Leroy A., committee member; Williams, Ron G., committee member (Colorado State University. Libraries, 1983)
The three major components of painting are concept, form, and process. The thesis paintings are the result of my effort to unify these three concerns. The works are intended to possess a quiet beauty that encourages extended visual interaction.
Keywords: Form perception